Review of Participatory Epizootiology research of contagious bovine pleuropneumonia at the department of veterinary public health and preventive medicine, University of Ibadan, Nigeria (2007- 2015) (2018)
This is a review of research application of Participatory Epizootiology to investigate Contagious Bovine Pleuropneumonia among pastoralists in Oyo State and Niger State, Nigeria, between 2007 and 2015, at the Department of Veterinary Public Health and Preventive Medicine, Faculty of Veterinary Medicine, University of Ibadan where the first author, a Veterinary Epidemiologist Lecturer/Researcher teaches Participatory Epizootiology Research as part of PVM 711: Advanced Epizootiology, a compulsory Course in the three Master degrees curriculum of the Department since 2004. He subsequently designed a PhD research project on the application of Participatory Epizootiology to the Igangan Grazing Reserve and got a University Senate Research SRG/FVM/2006/9A to that effect. In 2007, the Principal Veterinary Officer of the Faculty Eruwa Veterinary Field Station in Ibarapa East Local Government Area, Oyo State, south-western Nigeria, reported to the first author (then Chairman, Eruwa Veterinary Field Station), a suspected case of Contagious Bovine Pleuropneumonia incidence at the Igangan Grazing Reserve. The diseased lung samples of dead infected cattle he brought were confirmed by gross and histopathological examinations at the Faculty’s Department of Veterinary Pathology. From 2011 to 2015, the second author adopted the PE PhD-design (with other conventional veterinary research approach) to investigate Contagious Bovine Pleuro-pneumonia prevalence in Niger State, North-central Nigeria, first for his Masters (2011), followed with a PhD (2015). Result indicated that Contagious Bovine Pleuropneumonia in enzootic in Oyo and Niger State, Nigeria with a 77.67% of CBPP outbreaks in Niger State, Nigeria occurring in the dry season, and a prevalence of 8.73%. Participatory Epizootiology is a cheap, low capital involvement of traditional settler beneficiaries in identification of enzootic animal problems and their Community Based Animal Health training need. Participatory Epizootiology should be adopted in combination with conventional veterinary methods for effective Contagious Bovine Pleuropneumonia surveillance and control techniques in Africa.